CHAPTER 1 THE ENTRAINMENT, TRANSPORT AND SORTING OF HEAVY MINERALS BY WAVES AND CURRENTS - Komar P.D. (My University, 2007)
Heavy-mineral grains in a sediment have hydrodynamic properties that are distinct from the particles of quartz and feldspar. Differences also occur within the suite of heavy minerals due to their ranges of densities, diameters and shapes. The contrasting hydrodynamic properties of these sediment grains can give rise to differential rates of transport by flowing fluids that yield distinct patterns of deposition based on the particle attributes. The higher densities and generally finer grain sizes make the heavy minerals more resistant to entrainment by flowing water, and they then experience lower rates of transport when carried as part of the bedload or in suspension where differences in grain settling velocities are important. In the extreme this hydrodynamic sorting can lead to the formation of heavy-mineral concentrates, or a placer when the deposit contains economically valuable minerals. The processes of mineral sorting have been investigated mainly in the context of the formation of placers found in rivers, beaches and in continental shelf sands. That research is reviewed in application to the hydrodynamic sorting of sediment grains in general, with the focus being on the mechanisms of selective entrainment, shear sorting during bedload transport, sorting within the geometry of bedforms such as ripples, and the effects of differences in particle settling velocities on grain sorting during suspension transport and when the sediments are deposited. Each of these mechanisms depends on the particle density, diameter and shape, and collectively account for the observed patterns of mineral sorting found in sediment deposits. © 2007 Elsevier B.V. All rights reserved.
Keywords: BEACH PLACERS; CONTINENTAL SHELF SEDIMENTS; GRAIN ENTRAINMENT; GRAIN SETTLING VELOCITIES; PLACERS; RIVER PLACERS; SEDIMENT SORTING; SEDIMENT TRANSPORT